Způsoby interpretace společného historického původu tádžických Pamírců - Tomáš Retka (AntropoWebzin)
Collectively shared notion of a personal origin is often one of the sources of a group identity. For the Tajic Pamirs is a shared assumption of common origin one of the main arguments (the others are religion or language), by which they declare their peculiar identity. The members of the Pamirs groups derive their historical origin mainly from the times of the Hellenistic period in Central Asia.  Accordingly the Pamirs proclaim that their ethnogenesis is strongly influenced by the stay of Alexander the Greaťs army on their territory. Thus the Pamirs consider themselves (and sometimes they are considered also by the members of “non-Pamirs” groups) as the descendants of Alexander’s soldiers – more precisely of Alexander’s soldiers and local women (namely Aryan women). Nowadays such an assumption of common historical origin is indicated as one of the sources of defining within a scope of “we -they dichotomizing”. That is, we the Pamirs (descendants of Alexander the Great – shi´a ismá´ílics speaking Eastern Iranian languages) distinguish from the others „non-Pamirs“ who has different historical origin and religion, speaks distinct languages and partly has distinct material culture. The aim of the article is thus to analyze the phenomenon of proclaimed common origin mainly in context of the identity construction of the Pamirs. Main emphasis is put on the question: how this historical category is used not only within an academic or a political scope, but also within the popular models interpretations of social reality. Thus how it indicates in ordinary social interactions.